Legal transformation of the national perspective on civil unions and same sex marriage in Latin America - Cabrales Lucio, José Miguel (2015)
This paper analyzes the legal arguments that have been used toallow the gradual introduction of same-sex marriage and civil unions in some Latin American countries. The author makes a critical account of the contentious cases and legislative responses to claims for recognition and protection of human rights of people with a particular sexual orientation. The most representative Latin American countries are analyzed from the point of view of its relevance in comparative terms.